Mechanistic studies of Agmatine Deiminase from multiple bacterial species - Jones, Justin E. (2010)
One subfamily within the guanidino-group modifying enzymes (GMEs) is the agmatine Deiminases (AgD). These enzymes catalyze the conversion of agmatine (decarboxylated arginine) to N-carbamoyl putrescine and ammonia. In plants, viruses, and bacteria, these enzymes are thought to be involved in energy production, biosynthesis of polyamines, and biofilm formation. In particular, we are interested in the role that this enzyme plays in pathogenic bacteria. Previously we reported the initial kinetic characterization of the agmatine deiminase from Helicobacter pylori and described the synthesis and characterization the two most potent inactivators AgD inactivators. Herein we have expanded our initial efforts to characterize the catalytic mechanisms of AgD from H. pylori as well Streptococcus mutans, and Porphromonas gingivalis. Through the use of pH rate profiles, pK(a) measurements of the active site cysteine, solvent isotope effects, and solvent viscosity effects, we have determined that the AgDs, like PADs 1 and 4, utilize a reverse protonation mechanism.